2020
DOI: 10.3390/molecules26010001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dipeptidyl Peptidase-4 and α-Amylase Inhibitors from Melicope glabra (Blume) T. G. Hartley (Rutaceae) Using Liquid Chromatography Tandem Mass Spectrometry, In Vitro and In Silico Methods

Abstract: The present study investigated the antidiabetic properties of the extracts and fractions from leaves and stem bark of M. glabra based on dipeptidyl peptidase-4 (DPP-4) and α-Amylase inhibitory activity assays. The chloroform extract of the leaves was found to be most active towards inhibition of DPP-4 and α-Amylase with IC50 of 169.40 μg/mL and 303.64 μg/mL, respectively. Bioassay-guided fractionation of the leaves’ chloroform extract revealed fraction 4 (CF4) as the most active fraction (DPP-4 IC50: 128.35 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
14
2
Order By: Relevance
“…The binding affinity of compound 2 with α-amylase was lower than those previously reported for swermirin and methyl 3,4,5-trimethoxycinnamate in another study (Quek et al. 2020 ).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The binding affinity of compound 2 with α-amylase was lower than those previously reported for swermirin and methyl 3,4,5-trimethoxycinnamate in another study (Quek et al. 2020 ).…”
Section: Discussioncontrasting
confidence: 75%
“… 2018 ) and human DPP-4 complexed with drug sitagliptin (PDB ID 1X70) (Quek et al. 2020 ), both of which were retrieved from the Protein Data Bank ( https://www.rcsb.org/pdb ). AutodockTools (ADT) ver.…”
Section: Methodsmentioning
confidence: 99%
“…The chloroform extract of the leaves of M. glabra effectively inhibited DPP-4 with an IC 50 of 169.40 μg/mL. Computational analysis showed that compounds ( 8 ) and ( 7 ) in this extract are potent DPP-4 inhibitors based on their binding affinities and extensive interactions with important DPP-4 residues [ 93 ]. The phytochemical profiles of these compounds indicated their potential as DPP-4 inhibitors.…”
Section: Ddp-4 Inhibitors From Natural Sourcesmentioning
confidence: 99%
“…3.2.1.1) catalyze the hydrolysis of α -1,4 glycosidic bonds present in starch, glycogen and other related carbohydrates to low molecular weight products, such as glucose, maltose and maltotriose [ 4 , 5 , 6 , 7 , 8 ]. These enzymes are present in plants, animals and microorganisms [ 9 ] and have extensive applications in medicine [ 10 , 11 , 12 , 13 , 14 ], textiles [ 11 ], detergent [ 11 ], fermentation [ 11 ] and the food industry [ 4 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to industrial use, α -amylase from porcine pancreas is used for example in health food research [ 16 , 17 , 18 ], to assay resistant starch (RS), not broken down by human enzymes in the small intestine [ 19 ] and is also used in medical diagnostics [ 12 , 13 , 14 ]. One of the problems is effective diagnostic methods allowing for the prognosis of pancreatic cancer of cancer, which is an exceptionally aggressive tumour with high mortality.…”
Section: Introductionmentioning
confidence: 99%